STRATEGI BELAJAR ANAK BERPRESTASI DARI KELUARGA MISKIN DI SMAN 3 LENGAYANG KABUPATEN PESISIR SELATAN - Sari, Nopita; Erianjoni, Erianjoni; Fitlayeni, Rinel (Pendidikan Sosiologi, 2013)
Nopita Sari (09070024), Childrens Achievement and Learning Strategies From Poor Families In SMAN 3 Lengayang South Coastal District. Thesis Sociology Program Educational Studies High School Teaching and Education ( STKIP ) Sumatran PGRI weight , Padang , 2013This research Â examines about learning strategies achieving children from poor families in SMAN 3 Lengayang South Coastal District. In the learning process necessary facilities which sometimes costly, consequences for parents who are unable to fulfill that facilities, then the child will be late in the learning process, but not for children who excel from poor families that the author found in SMAN 3 Lengayang. It means that they can still get the achievement even though the economic conditions that limited the strategies they do. This study aims to describe the learning strategies achieving children in SMAN 3 Lengayang South Coastal District and describe the obstacles encountered achieving children from poor families in SMAN 3 Lengayang South Coastal District.The approach used in this study is a qualitative approach, which is trying to approach social reality that wish to study in depth and using qualitative data in the form of words and deeds. Informants of this study are the students who excel from poor families in SMAN 3 Lengayang South Coastal District. The selection of informants in this study using purposive sampling technique. Data used primary and secondary. Data collection techniques used were observation , interviews, documentation. The unit of analysis is the individual. Analysis of the data used includes three stages: 1 ) data reduction 2 ) presenting data 3 ) conclusion drawing or verification.Results of this study showed that children performed a variety of strategies for learning achievement such as 1 ) borrow books, among the others: the senior who has graduated, borrow books at the library, borrow books to a different school friends, borrow the book to the teacher 2 ) to repeat the lesson the teacher at the school, 3 ) for the materials and discuss the problems of the Internet, 4 ) form a study group. Then the constraints faced by students who excel , such as 1 ) divide difficult time in learning 2 ) lack of pleasure when one of my friends active in the learning process 3 ) is ridiculed by classmates for bringing lunch ( rice ) to school .